Kurikulum Pendidikan Islam di UIN Malang: Studi Pemikiran Imam Suprayogo dan M. Zainuddin - Firda Sofiana; Benny Afwadzi (At-Ta'lim : Media Informasi Pendidikan Islam, 2021)
In fact, the world of Islamic education has full of problems, both the dichotomy of sciences and the decline in morality and religiosity of Muslims, so efforts are needed to resolve these problems. In this article, the authors analize two figures from UIN Malang, namely Imam Suprayogo and M. Zainuddin towards this goal. The authors conclude that both thoughts are progressive and dynamic, have proactive and anticipatory educational insights in facing the accelerated development of science and technology, the demands of change, and are future oriented. The characteristics of his thinking appear in the need to develop an Islamic education curriculum into an integrated curriculum. Imam Suprayogo with his tree of knowledge, and M. Zainuddin with his Point Vortex Theory. Furthermore, their thoughts related to the Islamic education curriculum can be used as a consideration and reference to be actualized and implemented in the development of Islamic education institutions.